A Comparative Study between Conventional and Bethesda System for Reporting Thyroid Cytopathology - Azad, Shabana; Shah, Shaila N; Iyer, Rekha R (Annals of Pathology and Laboratory Medicine, 2018)
Background: Disorders of thyroid gland are very common. Thyroid cancers comprise 1% of all malignancies, and are the most common cancer of endocrine system. It is more common in females as compared to males. Method: 51 Patients with enlarged thyroid gland were studied. All the thyroid FNAC cases were reported and compared by using both the conventional and the Bethesda System for Reporting Thyroid Cytopathology (TBSTRC). The conventional system includes description of the microscopic findings of the case along with a final impression at the end. In equivocal cases, the differentials were given. However, for statistical analysis, the reporting system was modified into five category system. The categories were-1) Inadequate 2) Benign 3) Equivocal 4) Follicular 5) Malignant Results:The age at presentation of the patient varied widely from 10 years to 100 years. The mean age of presentation is 40 years. There was female preponderance amongst the patients (94.1% females). In the vast majority of the cases TBSRTC is equivalent to the conventional system in the pattern of reporting. Conclusion: TBSRTC may be viewed as a better screening test for thyroid lesions. Follicular patterned lesions pose the greatest difficulty in evaluating thyroid FNAC smears with their being significant overlap in the cytological features of different lesions.